Activation and Role of NACHT, LRR, and PYD Domains-Containing Protein 3 Inflammasome in RNA Viral Infection - Yu, Junyang; Wu, Yuzhang; Wang, Jingxue (Frontiers in Immunology, 2017)
NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome activation and effects during ribonucleic acid (RNA) viral infection are the focus of a wide range of research currently. Both the pathogen-associated molecule pattern derived from virions and intracellular stress molecules involved in the process of viral infection lead to activation of the NLRP3 inflammasome, which in turn triggers inflammatory responses for antiviral defense and tissue healing. However, aberrant activation of the NLRP3 inflammasome can instead support viral pathogenesis and promote disease progression. Here, we summarize and expound upon the recent literature describing the molecular mechanisms underlying the activation and effects of the NLRP3 inflammasome in RNA viral infection to highlight how it provides protection against RNA viral infection.